A translator as an author: on the dynamics of meaning behind "podróż" and "ruch" in the English translation of "Bieguni" by Olga Tokarczuk (Heteroglossia – studia kulturoznawczo-filologiczne, 2022)
The aim of this article is to examine the renderings of lexical items essential for the structure and the content of Tokarczuk’s ‘Bieguni’, i.e. podróż, and ruch, in the English translation performed by Jennifer Croft. Since we believe that both a wide-angle lens and a microscope are needed to view the composition properly, we offer both a qualitative and quantitative analysis of the terms in question. In particular, 78 instances of the use of podróż, and 80 instances of the use of ruch are subject to the scrupulous comparative analyses when it comes to their translated equivalents, providing an in-depth description of their context-embedded textual meanings, and an attempt to demonstrate that some of the translator’s choices befit the characteristics of explicitation.